Antioxidant activity of palm kernel meal protein hydrolysate and characterization of its peptide profile - SURANGKULWATTANA, Kavisara; HLOSRICHOK, Anirut; AUNPAD, Ratchaneewan (Food Science and Technology, 2023)
Palm kernel meal (PKM) is a major by-product of the palm oil industry, and its high protein content is a potential source of value-added functional food or feed. In this study, the total protein from PKM was isolated and hydrolyzed with alcalase enzyme (pH 7.5, 55oC) to obtain palm kernel protein hydrolysate. The results showed that PKM protein hydrolysate after 60 min of hydrolysis exhibited strong radical scavenging activity with IC50 values of 5.73±0.23 and 7.84±0.90 μg/mL as determined by 2,2-diphenyl-1-picrylhydrazyl and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), respectively. Furthermore, PKM protein hydrolysate was not toxic to mouse L929 fibroblast cells while protecting cells from H2O2-induced oxidative damage. Analysis of its peptide profile by liquid chromatography-mass spectrometry (LC-MS/MS) revealed nine peptide sequences with hydrophobic and negatively-charged amino acids with molecular weights ranging from 1,085.13 to 1,292.32 Da. Taken together, alcalase hydrolysate of PKM was found to have potent antioxidant and cytoprotective properties justifying further study for potential development as a functional food/feed.